2021
DOI: 10.3390/ijms222212336
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Comprehensive Analysis of the GASA Gene Family in Populus

Abstract: Gibberellic acid-stimulated Arabidopsis (GASA) proteins, as cysteine-rich peptides (CRPs), play roles in development and reproduction and biotic and abiotic stresses. Although the GASA gene family has been identified in plants, the knowledge about GASAs in Populus euphratica, the woody model plant for studying abiotic stress, remains limited. Here, we referenced the well-sequenced Populus trichocarpa genome, and identified the GASAs in the whole genome of P. euphratica and P. trichocarpa. 21 candidate genes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 86 publications
(132 reference statements)
1
28
0
Order By: Relevance
“…The CrGASAs were divided into three groups (G1, G2, and G3) based on their phylogenetic analysis with other species, including Arabidopsis, rice, and soybean ( Figure 2 ). According to this phylogenetic tree, most CrGASAs showed closer homology with soybean GASAs, and, as a diploid dicotyledon species, C. rosea holds more CrGASA members than that in the diploid monocotyledons—for example, 14 or 10 GASA members were found in maize and rice [ 28 , 32 ], while almost 20 GASA members were identified in apple (26), citrus (18), tobacco (18), and poplars (19 or 21), which probably indicates a slight GASA gene expansion in dicotyledon species [ 35 , 36 , 37 , 39 , 40 ]. Because of the relatively short protein lengths and the highly conserved GASA domains of all CrGASAs ( Figure 3 ), the classification of protein groups mostly depends on the variable N-terminus ( Figure 4 ), which also determines the subcellular localization of CrGASAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CrGASAs were divided into three groups (G1, G2, and G3) based on their phylogenetic analysis with other species, including Arabidopsis, rice, and soybean ( Figure 2 ). According to this phylogenetic tree, most CrGASAs showed closer homology with soybean GASAs, and, as a diploid dicotyledon species, C. rosea holds more CrGASA members than that in the diploid monocotyledons—for example, 14 or 10 GASA members were found in maize and rice [ 28 , 32 ], while almost 20 GASA members were identified in apple (26), citrus (18), tobacco (18), and poplars (19 or 21), which probably indicates a slight GASA gene expansion in dicotyledon species [ 35 , 36 , 37 , 39 , 40 ]. Because of the relatively short protein lengths and the highly conserved GASA domains of all CrGASAs ( Figure 3 ), the classification of protein groups mostly depends on the variable N-terminus ( Figure 4 ), which also determines the subcellular localization of CrGASAs.…”
Section: Discussionmentioning
confidence: 99%
“…Poplar is an important tree species for shelterbelt and timber forests, and there are 21 candidate GASA s in Populus trichocarpa and 19 in Populus euphratica . Some members are widely involved in hormone responses, growth, and development for vegetative organs, and drought stress responses [ 36 , 37 ]. Grapevine ( Vitis vinifera ) is a major fruit crop, and the demand for seedless grapes is greatly increasing.…”
Section: Introductionmentioning
confidence: 99%
“…GA2-oxidases (GA2oxs) regulate the deactivation of bioactive GAs and are very important to plant development and stress responses [ 54 ]. GASA ( Gibberellic Acid Stimulated in Arabidopsis ) genes encoding cysteine-rich peptides are involved in plant development and environmental adaption [ 55 ]. It has been reported that overexpression of GA2ox and GASA14 genes in Arabidopsis might enhance plants’ resistance to high salinity [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 ). Previous studies have revealed that the transcript of GASA from Populus euphratica is downregulated in leaves under MeJA treatment [ 33 ]. In Prunus mume, six GASA were upregulated after ABA treatment, and five GASA were upregulated at different time points after IAA treatment [ 34 ].…”
Section: Discussionmentioning
confidence: 99%